The potential of eco-tourism: a narrative case study of Perlis state park, Malaysia - W Omar Ali Saifuddin, Wan Ismail; Nur Aina Annisa, Anuwar; Shahrizal, Ahmad Sobri (2020)
Perlis eco-tourism industry emphasizes on its natural beauty compared to any manmade beauty. The charm of the recreational forests and the surreal appeal of the cave systems combined to provide an ecotourism destination succeeding in captivating scenery but unfortunately lacking in promotional expertise. This case study discusses the potential of eco-tourism at the Perlis State Park, which is still lacking as a renowned eco-tourism destination in the state of Perlis, Malaysia. The understanding of Perlis State Park has made it possible to be known as one of the potential eco-tourism spots and open to existing tourist needs and future tourists. In addition, the principle of eco-tourism is also discussed in order to increase understanding and gain more knowledge. Observations of several sites in the park, such as Gua Kelam, Gua Wang Burma and Gunung Perlis, have been made an effort to show the potential of eco-tourism and it is also to show the beauty of Perlis. Abundance of flora and fauna provides the opportunity to those who wish to research ecology. Therefore, in order to become one of the best eco-tourism destinations, the conservation of flora and fauna as well as sustainable tourism should be pursued on an ongoing basis.